Anti-inflammatory Action of Curcumin and Its Use in the Treatment of Lifestyle-related Diseases - Kana Shimizu; Masafumi Funamoto; Yoichi Sunagawa; Satoshi Shimizu; Yasufumi Katanasaka; Yusuke Miyazaki; Hiromichi Wada; Koji Hasegawa; Tatsuya Morimoto (European Cardiology Review)
Chronic inflammation plays a significant role in lifestyle-related diseases, such as cardiovascular diseases and obesity/impaired glucose tolerance. Curcumin is a natural extract that possesses numerous physiological properties, as indicated by its anti-inflammatory action. The mechanisms underlying these effects include the inhibition of nuclear factor-kappaB and Toll-like receptor 4-dependent signalling pathways and the activation of a peroxisome proliferator-activated receptor-gamma pathway. However, the bioavailability of curcumin is very low in humans. To resolve this issue, several drug delivery systems have been developed and a number of clinical trials have reported beneficial effects of curcumin in the management of inflammation-related diseases. It is expected that evidence regarding the clinical application of curcumin in lifestyle-related diseases associated with chronic inflammation will accumulate over time.